Pilot study of H2 therapy in Parkinson's disease: A randomized double‐blind placebo‐controlled trial. Issue 6 (11th February 2013) - Yoritaka, Asako; Takanashi, Masashi; Hirayama, Masaaki; Nakahara, Toshiki; Ohta, Shigeo; Hattori, Nobutaka
<x xml:space="preserve">Abstract</x> Background Oxidative stress is involved in the progression of Parkinson's disease (PD). Recent studies have confirmed that molecular hydrogen (H2) functions as a highly effective antioxidant in cultured cells and animal models. Drinking H2‐dissolved water (H2‐water) reduced oxidative stress and improved Parkinson's features in model animals. Methods In this a placebo‐controlled, randomized, double‐blind, parallel‐group clinical pilot study, the authors assessed the efficacy of H2‐water in Japanese patients with levodopa‐medicated PD. Participants drank 1, 000 mL/day of H2‐water or pseudo water for 48 weeks. Results Total Unified Parkinson's Disease Rating Scale (UPDRS) scores in the H2‐water group (n=9) improved (median, −1.0; mean±standard deviation, −5.7±8.4), whereas UPDRS scores in the placebo group (n=8) worsened (median, 4.5; mean±standard deviation, 4.1±9.2). Despite the minimal number of patients and the short duration of the trial, the difference was significant (P<0.05). Conclusions The results indicated that drinking H2‐water was safe and well tolerated, and a significant improvement in total UPDRS scores for patients in the H2‐water group was demonstrated. © 2013 Movement Disorder Society